Respuestas
Respuesta dada por:
0
Respuesta:
1) 30
2) 5
3) 16
4)18
Explicación paso a paso:
1. a*b=2a+b-3
12*8=2(12)+8-3
12*8=24+8-2
12*8=32-2
12*8=30
2. (Δx)=2x-3
(Δ8)=2(8)-3
(Δ8)=16-3
(Δ8)=13
(Оx)=3x+1
(О4)=3(4)+1
(О4)=12+1
(О4)=13
entonces:
√ (Δ8) + (О4) - 1
√ 13 + 13-1
√ 25
5
3. a∝b=5a-7b
4∝2=5(4)-7(2)
4∝2=20-14
4∝2=6
a∝b=5a-7b
6∝4=5(6)-7(4)
6∝4=30-28
6∝4=2
halla:
(4∝2) ∝ (6∝4)
(6 ∝ 2)
entonces:
aαb=5a-7b
6α2=5(6)-7(2)
6α2=30-14
6α2=16
4. (Δa)=
(Δ4)=
(Δ4)=16-4
(Δ4)=12
(Оb)=
(О3)=
(О3)=3-9
(О3)=-6
entonces:
(Δa) - (О3)
12 - (-6)
12+6
18
espero te sirva de ayuda :)
Preguntas similares
hace 5 años
hace 8 años
hace 8 años
hace 9 años
hace 9 años
hace 9 años